The adaptive value of flowering time in wild radish (Raphanus raphanistrum). Issue 2 (26th March 2021) - Sun, Ci; Ashworth, Michael B.; Flower, Ken; Vila-Aiub, Martin M.; Rocha, Roberto Lujan; Beckie, Hugh J.
Abstract: Harvest weed seed control (HWSC) is a weed management technique that intercepts and destroys weed seeds before they replenish the soil weed seedbank and can be used to control herbicide-resistant weeds in global cropping systems. Wild radish ( Raphanus raphanistrum L.) is a problematic, globally distributed weed species that is considered highly susceptible to HWSC, as it retains much of its seed on the plant during grain harvest. However, previous studies have demonstrated that R. raphanistrum is capable of adapting its life cycle, in particular its flowering time, to allow individuals more time to mature and potentially shed seeds before harvest, thereby evading HWSC interception. This study compared the vegetative growth plus physiological and ecological fitness of an early-flowering R. raphanistrum biotype with an unselected genetically related biotype to determine whether physiological costs of early flowering exist when in competition with wheat ( Triticum aestivum L.). Early flowering time adaptation in R. raphanistrum did not change the relative growth rate or competitive ability of R. raphanistrum . However, the height of first flower was reduced in the early flowering time–selected population, indicating that this population would retain more pods below the typical harvest cutting height (15 cm) used in HWSC. The presence of wheat competition (160 to 200 plants m −2 ) increased flowering height in the early flowering time–selected population, which would likely increase the susceptibility of early-flowering R. raphanistrum plants to HWSC. Overall, early-flowering adaption in R. raphanistrum is a possible strategy to escape being captured by the HWSC; however, increasing crop competition is likely to be an effective strategy to maintain the effectiveness of HWSC.